Readiness towards Self-Directed Learning among Bachelor Level Nursing Students in a Campus, Banke District - Sashi, Radhika; Acharya, Sunita; Nai, Saraswati (MALATA SAINS INDONESIA, 2024)
Introduction: Self-directed learning is beneficial in adult learning and is associated with better outcomes, particularly through lifelong learning processes. Objective: This study's main objective was to assess the level of readiness towards self-directed learning among bachelor-level students at a Nepalgunj nursing campus. Method: A descriptive cross-sectional study based on a quantitative approach research design was used in this study. Structured self - administered questionnaire was used to collect data among the students based on an internationally validated tool of the self-directed learning readiness scale (SDLRS) developed by Fisher et al 2001. The collected data was analyzed by Statistical Package for Social Science (SPSS) version 24. Descriptive statistics (frequency & percentage) and inferential statistics (Chi-squire test) were used for data analysis. Results: This study revealed that most (87.2%) of the students have a high level of readiness for self-directed learning. A significant association was found between age, type of family, academic years, and voluntary selection of nursing education of students with the level of readiness for Self Directed Learning among bachelor-level nursing students. The score of subscale self-control is higher than self-management and desire for learning. Conclusion: The study concluded that most of the students have a high level of readiness for self-directed learning.